Indigenous Experience as a Strategy to Develop Rural Tourism Identity - Heni Indrayani; Candra Yudha Satriya; Astini Kumalasari (Universitas Gadjah Mada, 2021)
Rural tourism is often seen as a tourist attraction, where tourists make their visit only to catch a glimpse of the village’s potential. In contrast to this trend, the rural tourism of in Tanon sub village of in the Semarang regency (Central Java) attempts to offer more by developing its local strength as “Desa Menari” (lit. Dancing Village). It offers tour packages that invite tourists to experience a life in the village, interact with local communities, find happiness, and reinterpret life. The objective of this study is to find out how the local community uses indigenous experience as a strategy to develop rural tourism in the area. This study implemented the communication theory of identity (CTI) by applying qualitative method with a case study approach. After observation and in-depth interview were conducted to rural tourism community, this study found that rural tourism community actively introduces tourism based on local wisdom experiences through the conservation of tourism in Dusun Tanon, including the conservations of community arts, traditional games, and farmer. Indigenous experience as a village identity is constructed according to its purpose, i.e. spreading harmony, knitting inspiration, and reaping memory. This village identity includes personal identity, relational identity, and enacted identity that invite tourists to capture the process of self-meaning or journey into oneself as a psychological experience.